2004
DOI: 10.1111/j.1537-2995.2004.03389.x
|View full text |Cite
|
Sign up to set email alerts
|

A new automated cell washer device for thawed cord blood units

Abstract: The Cytomate device demonstrated a satisfying efficiency in cell recovery and in maintaining the clonogenic power of the UCB graft. The removal rate of DMSO was practically complete with evident advantages for the recipient. Finally, the entire manipulation performed in a closed system revealed to be safe, maintaining the sterility of the graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Antonenas et al (2002) observed a loss of 27-30% of nucleated cells due to postthaw washing of umbilical cord blood. Perotti et al (2004) observed a similar loss. Laroche et al (2005) suggested that the wash step be omitted particularly in certain categories of patients where the loss of cells may have a detrimental effect.…”
Section: Introductionsupporting
confidence: 71%
“…Antonenas et al (2002) observed a loss of 27-30% of nucleated cells due to postthaw washing of umbilical cord blood. Perotti et al (2004) observed a similar loss. Laroche et al (2005) suggested that the wash step be omitted particularly in certain categories of patients where the loss of cells may have a detrimental effect.…”
Section: Introductionsupporting
confidence: 71%
“…Many in vitro studies have reported that the freezing phase can lower by as much as 30% the viability and functional capacity of the cryopreserved product [8][9][10][11]. In the present study, whose aim was to evaluate the manual method of thawing described by Rubinstein et al [8], we obtained a cell viability of approximately 73%.…”
Section: Discussionmentioning
confidence: 96%
“…Quantifying CD34+ cell content in frozen and thawed HSC products is also challenging for some of the same reasons described above. For example, studies have reported CD34+ cell recovery of >100% and as high as 200% [65,94]. There is no evi-dence that the freezing process spurs proliferation of HSCs.…”
Section: Post-thaw Assessmentmentioning
confidence: 99%
“…Losses of 27-30% of nucleated cells were observed by Antonenas and colleagues [61], with slightly lower losses observed in a subsequent study [64] using modified centrifugation technique to maximize cell recovery. Using an automated cell washer to remove DMSO from frozen and thawed cord blood resulted in similar losses [65]. Technologies have been developed for the removal of CPA solutions from frozen and thawed blood cells (not HSC products).…”
Section: Emerging Technologymentioning
confidence: 99%